THE IMPACT OF THE CHARACTERISTICS OF THE BOARD OF DIRECTORS ON THE PERFORMANCE OF THE ALGERIAN BANKS - Touahri, Mohammed (Journal of Research in Finance and Accounting, 2026)
The purpose of this research is to analyze the impact of the characteristics of the board of directors (the size of the board, the PCA / CEO duality, the frequency of meetings and the presence of external directors) on the performance of Algerian commercial banks, measured by the (ROA). The empirical validation concerning a panel built from 12 Algerian commercial banks observed for a period of 12 years, from 2008 to 2019. The results shows that the size of the board of directors, the duality of management and the size of the bank negatively influence the performance of these banks. On the other hand, the level of debts influence positively this performance. However, the presence of independent directors and the frequency of meetings have no impact on the performance of the Algerian banks.